Differential Physiological and Metabolic Responses to Drought Stress of Peanut Cultivars and Breeding Lines. Issue 5 (1st September 2014) - Singh, Daljit; Collakova, Eva; Isleib, Thomas G.; Welbaum, Gregory E.; Tallury, Shyam P.; Balota, Maria
ABSTRACT: The Virginia–Carolina region is the most important peanut ( Arachis hypogaea L.) production region for the large‐seeded, virginia‐type peanut in the United States, but 85% of the production is rainfed and predisposed to water deficit stress. The mechanisms virginia‐type peanut uses in response to drought stress are poorly understood. We evaluated several physiological and metabolic characteristics and their relationship with pod yield in eight virginia‐type cultivars and advanced breeding lines in rainfed and irrigated field trials in 2011 and 2012. Each year, evaluations were performed at three sampling dates in conjunction with growth stages beginning flower, pod, and seed. Significant ( p ≤ 0.05) genotypic variation in membrane injury, chlorophyll fluorescence ( F v / F m ratio), and relative levels of metabolites and lipid‐derived fatty acids was observed in response to water regime and sampling time. In general, in both years, the F v / F m ratio, organic acids, and fatty acids decreased in rainfed vs. irrigated plants, while the relative levels of sugar and cyclic polyols increased. Because higher levels of organic acids and lower levels of sugars were associated ( p ≤ 0.05) with higher pod yield, we conclude that natural stress responses rather than adaptive mechanisms to drought prevailed for the genotypes used in this study. Based on its minimal changes in the F v / F m ratio and metabolite levels of the rainfed vs. irrigated plants, line SPT 06‐07 showed improved tolerance to water deficit stress; this line can be an important source for drought tolerance improvement of the virginia‐type peanut.